An Overview on Romanian Strategies regarding Roma Minority Concerning Education and Employment - Patache, Laura; Negurita, Octav (Journal of Economic Development, Environment and People, 2020)
According to the Council of Europe, Roma population in Romania is about 8.6% representing the largest minority group, exceeding the Hungarian ones. Demographic trends make the problem of the Roma minority even more stringent, through the fact that the population is aging despite of Roma’s positive natural increase. Romanian Government elaborated a Strategy to improve conditions for the Roma, which is permanently updated according to political commitment at the international level, based on the following guiding principles: consensuality, social utility, sectorial division, decentralization in execution, legislative compatibility, identity differentiation, and equality. The education is the key to a better access to the labor market and in last two decades authorities have taken several actions concerning Roma social inclusion, but the results are not the ones expected. It is a fact that, especially in case of children, low life’s level, marginalized communities, rural area, culture and traditions may generate socially exclusion and inequality. The study aims to make an overview of the Romanian governmental policies regarding the improvement of the situation of the Roma minority, especially regarding education and employment. The results of the study could be useful for a better correlation of social policies with impact on living of Roma.